Contrasting Fates of Petrogenic and Biospheric Carbon in the South China Sea. Issue 17 (6th September 2018) - Blattmann, T. M.; Zhang, Y.; Zhao, Y.; Wen, K.; Lin, S.; Li, J.; Wacker, L.; Haghipour, N.; Plötze, M.; Liu, Z.; Eglinton, T. I.
Abstract: A synthesis of published and newly acquired stable and radiocarbon isotope data from soil, river, and marine particulate organic carbon (OC) from the South China Sea drainage and sedimentary basin reveals that OC derived from bedrock‐erosion (petrogenic OC) and marine productivity comprises the major contributors to bulk OC in particulate matter reaching abyssal depths, while soil‐derived OC appears negligible. Aluminum‐radiocarbon relationships of sediments suggest that soil OC initially associated with detrital terrestrial minerals is lost and replaced by marine OC during transport beyond the continental shelf. We estimate that petrogenic OC sinking to a 30, 000 km 2 region of the deep northeastern South China Sea accounts for 0.6% of global petrogenic OC burial. The basin‐wide OC isotope patterns coupled with sediment trap observations highlight both the spatial variabilities of OC components as they propagate from source to sedimentary sink and the significance of petrogenic OC to deep ocean sediments. Plain Language Summary: Sediment traps deployed in the ocean intercept settling particulate organic matter of marine and terrestrial origin. Terrestrial organic matter includes contributions from soils as well as bedrock‐derived organic matter mobilized by erosional processes and is exported by rivers into the ocean, where it contributes to sinking sediment fluxes. In this sediment trap study from the northeastern South China Sea, we constrain the flux and type of organic carbon exported to the deep ocean using stable and radiocarbon isotopes. We find that bedrock‐derived and marine organic matter comprise the dominant types of sedimentary organic matter reaching the deep South China Sea, whereas soil organic matter is conspicuously absent. Both bedrock‐derived carbon and marine carbon are associated with terrestrial mineral particles as revealed by the high aluminum contents of all collected sediments, implying that soil organic matter must be lost from mineral surfaces and replaced with marine carbon. These findings raise fundamental new questions concerning the role of organic matter‐mineral interactions in the ocean. Key Points: Marine and petrogenic OC dominantly contribute to bulk POC in abyssal sediments Soil OC is absent in deep‐sea sediments due to preferential loss and deposition on proximal shelf Al‐ 14 C trend indicates loss of soil OC from lithogenic particles with lowest 14 C values thus far reported for deep ocean POC